2010
DOI: 10.1186/1471-2415-10-16
|View full text |Cite
|
Sign up to set email alerts
|

A survey of visual function in an Austrian population of school-age children with reading and writing difficulties

Abstract: BackgroundTo describe and compare visual function measures of two groups of school age children (6-14 years of age) attending a specialist eyecare practice in Austria; one group referred to the practice from educational assessment centres diagnosed with reading and writing difficulties and the other, a clinical age-matched control group.MethodsRetrospective clinical data from one group of subjects with reading difficulties (n = 825) and a clinical control group of subjects (n = 328) were examined.Statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 28 publications
2
73
2
Order By: Relevance
“…Our findings are comparable with previous reports suggesting that children with visual function anomalies could be at disadvantage in reading, writing and academic performance [5,12,13,25,[29][30][31][32][33][34]. Some studies support the possibility that children with unstable binocular control commit more phonological spelling errors, even when age, IQ and phonemic awareness were taken into account [29].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Our findings are comparable with previous reports suggesting that children with visual function anomalies could be at disadvantage in reading, writing and academic performance [5,12,13,25,[29][30][31][32][33][34]. Some studies support the possibility that children with unstable binocular control commit more phonological spelling errors, even when age, IQ and phonemic awareness were taken into account [29].…”
Section: Resultssupporting
confidence: 82%
“…Previous research on refractive status and reading performance suggested that myopic children are better readers than hyperopic children [10,38]. However, other studies [25,40] do not found any association between refractive error and reading in children.…”
Section: Resultsmentioning
confidence: 39%
See 1 more Smart Citation
“…Children with reading and writing problems have been found to have both reduced accommodation and impaired convergence. 5 We have previously reported a reduced near visual acuity in the same study population as in the present study, even when children with previous ROP and neurological complications were excluded. 12 The present study could not explain this finding, since no correlations between accommodation or convergence and near visual acuity were found.…”
Section: Discussionmentioning
confidence: 73%
“…4 Studies on typically developing children have found a higher prevalence of reduced accommodation and convergence in children with reading and writing disabilities. 5 There are only few studies published on accommodation and near-point convergence in prematurely born children. Dowdeswell et al 6 examined the convergence in 86 children and Lindqvist et al 7 assessed both accommodation and convergence in 51 teenagers.…”
Section: Introductionmentioning
confidence: 99%